Utilization of evidence-based tools and medical education literature by Canadian postgraduate program directors in the teaching and assessment of the CanMEDS roles - Doja, Asif; Eady, Kaylee; Warren, Andrew; Wiesenfeld, Lorne; Writer, Hilary (Canadian Medical Education Journal, 2020)
Background: Researchers have shown that clinical educators feel insufficiently informed about how to teach and assess the CanMEDS roles. Thus, our objective was to examine the extent to which program directors utilize evidence-based tools and the medical education literature in teaching and assessing the CanMEDS roles. Methods: In 2016, the authors utilized an online questionnaire to survey 747 Canadian residency program directors (PD’s) of Royal College of Physicians and Surgeons of Canada (RCPSC) accredited programs. Results: Overall, 186 PD’s participated (24.9%). 36.6% did not know whether the teaching strategies they used were evidence-based and another third (31.9%) believed they were “not at all” or “to a small extent” evidence-based. Similarly, 31.8% did not know whether the assessment tools they used were evidence-based and another third (39.7%) believed they were “not at all” or “to a small extent” evidence-based. PD’s were aware of research on teaching strategies (62.4%) and assessment tools (51.9%), but felt they did not have sufficient time to review relevant literature (72.1% for teaching and 64.1% for assessment). Conclusions: Canadian PD’s reported low awareness of evidence-based tools for teaching and assessment, implying a potential knowledge translation gap in medical education research.